FAKTOR-FAKTOR YANG MEMENGARUHI KEMAUAN MEMBAYAR PAJAK WAJIB PAJAK ORANG PRIBADI YANG MELAKUKAN PEKERJAAN BEBAS (STUDI KASUS PADA KPP PRATAMA KOTA PEKALONGAN) - Dian Prihatiningsih (Jurnal Ekonomi Dan Bisnis, 2020)
This study aims to analyze the factors that affect the willingness to pay taxes on taxpayers of individuals who perform free work in the office of KPP Pratama Pekalongan. The variables in this study are taxpayer willingness as dependent variable knowledge of taxation regulation, understanding of tax regulation, good perception on tax system and level of trust to government system and law as independent variable. The population in this study were free workers registered in KPP pratama stem. The sample used in this research is as many as 63 respondents are free workers registered in KPP pratama stem. Meanwhile, to answer the hypothesis in this research is done classical assumption test and multiple linear regression. The result of the research shows that variable knowledge of tax regulations, understanding of tax regulations, a good perception of the effectiveness of the taxation system has a significant effect on willingness to pay taxes but for the level of trust in the government and the legal system has no significant effect on willingness to pay taxes. Keywords: knowledge of tax regulations, understanding of tax laws, good perceptions of the effectiveness of the tax system and the degree of confidence in government and legal systems.